Pengaruh Peran Guru Terhadap Peningkatan Akhlakul Karimah Siswa Di Kelas Vlllc Mts Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan - Dina Al Adawia; Nurul Aslamiyah; Ami Latifah (Penerbit Widina, Widina Media Utama, 2026)
The first objective of this study was to determine the influence of the teacher's role on improving the morality of class VIIIC students at MTs Hidayatul Mubtadiin Sidoharjo, Jati Agung, South Lampung. The second objective was to determine the impact of the teacher's role on improving the morality of class VIIIC students at MTs Hidayatul Mubtadiin Sidoharjo, Jati Agung, South Lampung. This study used a quantitative approach with an associative correlational type to analyze the influence of the teacher's role on the morality of class VIIIC students at MTs Hidayatul Mubtadiin Sidoharjo, South Lampung. The entire student population (n=24) was sampled through total sampling. Data were collected using a Likert scale questionnaire, observation, and documentation, and tested for validity and reliability with SPSS 23. Before testing the hypothesis, normality and linearity tests were conducted. Analysis was conducted using simple linear regression and t-test to determine the extent of the influence of the teacher's role on students' morality. The results of this study indicate that the role of teachers has a significant influence on the moral character of class VIII C students at MTs Hidayatul Mubtadiin Sidoharjo. A simple linear regression analysis showed that every one-unit increase in the teacher's role was followed by a 1.032-unit increase in moral character (Sig. 0.003 0.05), with an R-square value of 42.3%, indicating the teacher's contribution in shaping students' moral behavior. This finding supports Bandura's theory of social learning and the Islamic educational perspective on teacher guidance as a model of morality. The success of character formation is also influenced by the school environment, family, and social interactions, emphasizing the importance of a holistic approach in character education to produce intelligent and noble students.ABSTRAKTujuan Penelitian ini yang pertama yaitu untuk mengetahui pengaruh peran guru terhadap peningkatan Akhlakul karimah siswa kelas VIIIc MTs Hidayatul Mubtadiin Sidoharjo, Jati Agung, Lampung Selatan Dan yang kedua yaitu Untuk mengetahui adanya dampak dari pengaruh peran guru terhadap peningkatan Akhlakul karimah siswa VIIIc MTs Hidayatul Mubtadiin Sidoharjo, Jati Agung, Lampung Selatan. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis asosiatif korelasional untuk menganalisis pengaruh peran guru terhadap akhlakul karimah siswa kelas VIII C MTs Hidayatul Mubtadiin Sidoharjo, Lampung Selatan. Populasi seluruh siswa (n=24) dijadikan sampel melalui total sampling. Data dikumpulkan menggunakan angket skala Likert, observasi, dan dokumentasi, serta diuji validitas dan reliabilitas dengan SPSS 23. Sebelum pengujian hipotesis, dilakukan uji normalitas dan linearitas. Analisis dilakukan menggunakan regresi linier sederhana dan uji t untuk mengetahui besarnya pengaruh peran guru terhadap akhlakul karimah siswa. hasil penelitian Ini menunjukkan bahwa peran guru terbukti memiliki pengaruh signifikan terhadap akhlakul karimah siswa kelas VIII C MTs Hidayatul Mubtadiin Sidoharjo. Analisis regresi linier sederhana menunjukkan setiap peningkatan satu satuan pada peran guru diikuti peningkatan akhlakul karimah sebesar 1,032 satuan (Sig. 0,003 0,05), dengan nilai R Square 42,3%, menunjukkan kontribusi guru dalam membentuk perilaku moral siswa. Temuan ini mendukung teori Bandura tentang social learning dan pandangan pendidikan Islam mengenai bimbingan guru sebagai model akhlak. Keberhasilan pembentukan karakter juga dipengaruhi lingkungan sekolah, keluarga, dan interaksi sosial, menegaskan pentingnya pendekatan holistik dalam pendidikan karakter untuk menghasilkan siswa cerdas dan berakhlak mulia.